2016
DOI: 10.1002/pds.4052
|View full text |Cite
|
Sign up to set email alerts
|

Association between statins and infections among patients with diabetes: a cohort and prescription sequence symmetry analysis

Abstract: PurposeA previous meta‐analysis of randomized trials did not confirm findings from observational studies that suggested that statins reduce the risk of infection. However, animal experiments indicate that statins may be more effective in reducing the risk and/or the severity of infection among patients with diabetes. Hence, we evaluated the effect of statins on antibiotic prescriptions (a proxy for infections) among patients with drug‐treated type 2 diabetes using two confounding‐reducing observational designs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
10
2
1
Order By: Relevance
“…The findings of this study were in contrast to those reported by Pouwels et al ., who reported a reduction in antibiotic use in drug‐treated type 2 diabetic statin users compared to nonusers. Although their research design also utilised SSA, they did not examine the effects of narrow spectrum antibiotics (such as dicloxacillin and flucloxacillin), which target mainly staphylococci, a major bacterial causative agent for SSTIs .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The findings of this study were in contrast to those reported by Pouwels et al ., who reported a reduction in antibiotic use in drug‐treated type 2 diabetic statin users compared to nonusers. Although their research design also utilised SSA, they did not examine the effects of narrow spectrum antibiotics (such as dicloxacillin and flucloxacillin), which target mainly staphylococci, a major bacterial causative agent for SSTIs .…”
Section: Discussioncontrasting
confidence: 99%
“…Marker drugs used were antidiabetic medication (insulins, insulin analogues and oral blood glucose lowering drugs) SSTIs (Figure 5), alluding to statin use as an important contributor to SSTI risk. Viewed collectively, it may be posited that statins are associated with an increased SSTI risk, whether via direct nondiabetogenic mechanisms (Figure 1: direction [i]), or via indirect diabetogenic mechanisms (Figure 1: directions [ii] and [iii]).The findings of this study were in contrast to those reported by Pouwels et al,18 who reported a reduction in antibiotic use in drugtreated type 2 diabetic statin users compared to nonusers. Although their research design also utilised SSA, they did not examine the effects of narrow spectrum antibiotics (such as dicloxacillin and flucloxacillin), which target mainly staphylococci, a major bacterial causative agent for SSTIs 1.…”
contrasting
confidence: 86%
See 2 more Smart Citations
“…The results of animal and in vitro studies suggest that statins may be more effective against infections among diabetic patients than among patients without diabetes, by reducing Rac1 activation and/or inhibiting biofilm formation (5-9). Moreover, among patients without diabetes, the potentially smaller benefits may be outweighed by the increased risk of incident diabetes among statin users (5,10).…”
mentioning
confidence: 99%